2017
DOI: 10.1037/pri0000037
|View full text |Cite
|
Sign up to set email alerts
|

An international perspective on criminal responsibility and mental illness.

Abstract: Criminal responsibility refers to the degree to which an individual is accountable for an illegal act that he or she committed given idiographic factors such as age, cognitive abilities, and psychological functioning (Packer, 2009). Thus, perception of criminal responsibility has the potential to greatly impact forensically involved individuals, and most often forensically involved individuals living with severe and persistent mental illness and/or cognitive limitations. This paper focuses on international and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
0
8
0
4
Order By: Relevance
“…Such evaluations are perhaps the most challenging for mental health professionals [ 1 , 2 ]. In most jurisdictions, an opinion of criminal irresponsibility can only be reached if a severe mental disorder is present, but not all disorders qualify [ 3 5 ]. Studies have shown that psychotic disorders are most often connected to CR [ 1 , 4 11 ], but even when there is proof of a severe mental disorder, most penal codes require that a connection be made between the disorder and the defendant’s actions at the time of the offense [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such evaluations are perhaps the most challenging for mental health professionals [ 1 , 2 ]. In most jurisdictions, an opinion of criminal irresponsibility can only be reached if a severe mental disorder is present, but not all disorders qualify [ 3 5 ]. Studies have shown that psychotic disorders are most often connected to CR [ 1 , 4 11 ], but even when there is proof of a severe mental disorder, most penal codes require that a connection be made between the disorder and the defendant’s actions at the time of the offense [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…akıl hastalığı temeline dayanan bir savunma oluşturmak için, suçun işlendiği sırada eylemi gerçekleştiren tarafın zihinsel yetersizlik veya akıl hastalığına bağlı olarak yaptığı eylemin doğasını ve niteliğini bilmediğinin veya yaptığının yanlış olduğunu bilmediğinin açıkça kanıtlanması gerektiğini" belirtmiştir (4). Bir suç eyleminden yasal olarak sorumlu olmak için, davalının (i) ne yaptığını bildiğini ve (ii) yaptığı şeyin yanlış olduğunu bilmesi gerektiğini içeren M'Naughten Kuralları ve varyasyonları Amerika, İngiltere, Kanada, Avustralya, Portekiz ve Yeni Zelenda gibi hukuk sistemlerinde kullanılmaya başlanmıştır (5-7) Bu ülkelerde ruhsal bozukluğu olan ve akıl hastalığı savunmasında bulunan bireylerin adli ruh sağlığı uzmanlarınca suç sırasında akıl hastalığının etkisinde olup olmadıkları belirlenerek ceza sorumluluğunun olduğu veya olmadığı yönünde iki uçlu bir tespite gidilmektedir (6,7). Bu iki uçlu değerlendirmeden farklı olarak Hollanda, Belçika, Almanya, Yunanistan, Çin gibi ülkelerde ceza sorumluluğu derecelendirmiş bir ölçeğe göre belirlenir.…”
Section: Introductionunclassified
“…Bu iki uçlu değerlendirmeden farklı olarak Hollanda, Belçika, Almanya, Yunanistan, Çin gibi ülkelerde ceza sorumluluğu derecelendirmiş bir ölçeğe göre belirlenir. Örneğin Hollanda'da bir suçlunun ceza sorumluluğu; tam sorumluluk, hafif azalan sorumluluk, azalan sorumluluk, ciddi biçimde azalan sorumluluk ve tam sorumsuzluk olarak 5 dereceye dayanarak belirlenirken Yunanistan ve Çin'de tam sorumluluk, azalan sorumluluk ve tam sorumsuzluk olarak 3 dereceye dayanarak belirlenir (6,8,9). İsveç'te ise "akıl hastalığı nedeniyle suçsuzluk" (not guilty by reason of insanity) kavramı olmayıp "suçlu fakat akıl hastası" (guilty but insane) kavramı bulunmaktadır.…”
Section: Introductionunclassified
See 2 more Smart Citations